Impacts of Ride Sharing Apps among the Youths of Kathmandu Valley - Shrestha, Jasmine; Pradhan, Sumit (Nepalese Journal of Management, 2025)
The study examines the impacts of ride sharing apps among the youths of the Kathmandu Valley. Attitude towards using ride sharing apps is selected as the dependent variables. The selected independent variables ease of use, privacy concerns, time management, price and convenience. The primary source of data is used to assess the opinions of respondents regarding ease of use, privacy concerns, time management, price and convenience and attitude of youths towards using ride sharing apps. The study is based on primary data of 163 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and impacts of ride sharing apps among the youths of the Kathmandu Valley. The study showed that ease of use is positively correlated to attitude towards using ride sharing apps. It indicates that ease of use leads to an increase in attitude towards using ride sharing apps. Likewise, privacy concern is positively correlated to attitude towards using ride sharing apps. It indicates that privacy concern has a positive impact on attitude towards using ride sharing apps. Further, time management is positively correlated to attitude towards using ride sharing apps. It indicates that time management leads to an increase in attitude towards using ride sharing apps. Additionally, price and convenience also demonstrate positive correlations with attitude towards using ride sharing apps., suggesting their significant roles in shaping the use of ride sharing apps in the Kathmandu Valley.